Carbon coated nickel - Nickel oxide composites as a highly efficient catalyst for hydrogen evolution reaction in acid medium. (20th February 2018) - Chu, Mei; Wang, Lu; Li, Xi; Hou, Meijing; Li, Na; Dong, Yongzhi; Li, Xiaozheng; Xie, Zhizhong; Lin, Yawei; Cai, Weiquan; Zhang, Chaocan
Abstract: Carbon coated nickel - nickel oxide composites (Ni/NiO@C/GR- t - w ) was synthesized from the direct carbonization of the composites composed of Ni-MOF-74 and graphene oxide (GO). Due to the synergetic effects of Ni, NiO and graphene, Ni/NiO@C/GR- t - w all exhibited the electrocatalytic performance to HER in acidic medium. When the GO content was 8% and the carbonization temperature was 900 °C, the composites (Ni/NiO@C/GR-900-8) showed the best electrocatalytic properties with an lower overpotential of 108 mV ( vs . RHE) at 10 mA cm −2, a smaller Tafel slope of 44 mV dec −1 and a good stability in a 0.5 M H2 SO4 solution. The excellent electrocatalytic performance enabled Ni/NiO@C/GR composites to be a favorable HER catalyst to replace the expensive Pt-based materials in the applications of the hydrogen production. Graphical abstract: Highlights: Composites Ni/NiO@C/GR were synthesized by direct carbonization of MOF-74/GO hybrids. Ni/NiO@C/GR-900-8 showed excellent electrocatalytic activity to HER in acidic medium. Overpotential at 10 mA cm −2 was 108 mV ( vs. RHE). Onset potential and Tafel slope of HER was −34.7 mV and 44 mV dec −1, respectively. Potential hardly shifted during 24 h experiment, indicating good stability.